2001
DOI: 10.1207/s15516709cog2501_2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative visual search: a difference that makes a difference

Abstract: In this article we present a new experimental paradigm: comparative visual search. Each half of a display contains simple geometrical objects of three different colors and forms. The two display halves are identical except for one object mismatched in either color or form. The subject's task is to find this mismatch. We illustrate the potential of this paradigm for investigating the underlying complex processes of perception and cognition by means of an eye‐tracking study. Three possible search strategies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 31 publications
5
33
0
1
Order By: Relevance
“…We have found that fixations occur in two phases, as others have reported [Pomplun et al 2001b;Rayner 1998;Kundel 2004]. The first phase (search phase), occurs while the subject is searching the whole image for a suspicious object, or a likely target.…”
Section: Eyegaze Search Patterns and Trial Outcomesupporting
confidence: 52%
See 1 more Smart Citation
“…We have found that fixations occur in two phases, as others have reported [Pomplun et al 2001b;Rayner 1998;Kundel 2004]. The first phase (search phase), occurs while the subject is searching the whole image for a suspicious object, or a likely target.…”
Section: Eyegaze Search Patterns and Trial Outcomesupporting
confidence: 52%
“…Pomplun [Pomplun et al 2001a[Pomplun et al , 2001bPomplun and Ritter 1999], have studied eyegaze patterns during comparative visual search tasks, although picture-matching tasks involving recognition of the same object within two pictures have been much studied [Humphrey and Lupker 1993]. Like other researchers such as Kundel [2004] have reported, Pomplun et al found that there are two phases of visual search-a first phase of search and comparison, and a second phase of detection and verification.…”
Section: Eyegaze Patterns During Comparative Visual Search Only a Fementioning
confidence: 99%
“…Pomplun et al, 2001). Participants were shown displays with a goalkeeper positioned (marginally) off-centre and were instructed to identify which half of the goal is the bigger one, necessitating the participants to compare both sides of the goal.…”
Section: Methodsmentioning
confidence: 99%
“…A general discussion of costs in terms of time requirements has been given by Gray, Sims, Fu, and Schoelles (2006). To investigate the trade-off between the usage of VSTM and the execution of eye movements, Inamdar and Pomplun (2003) used a comparative visual search paradigm developed by Pomplun et al (2001). In their study, two identical columns of simple geometrical objects (each column containing 20 objects) had to be compared to detect the single difference (target).…”
Section: Introductionmentioning
confidence: 99%